1960
DOI: 10.1039/df9602900137
|View full text |Cite
|
Sign up to set email alerts
|

II(a). Oxidation-reduction reactions involving inorganic substrates. Aqueous chemistry of inorganic free radicals. Part 3.—The kinetics and mechanism of the reaction of peroxydisulphate ion and hydrogen peroxide

Abstract: A kinetic study has been made of the reaction of peroxydisulphate ion and hydrogen peroxide in aqueous solution at 30°C. In three different ranges of concentration of the reactants the rate law approaches three different limiting forms : (i) first order in peroxydisulphate and half order in hydrogen peroxide, (ii) first order in peroxydisulphate and (iii) half order in peroxydisulphate. The proposed mechanism involves a chain reaction, with the SO,-, OH, and H02 radicals carrying and terminating the reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A multiradical attack mechanism was proposed to explain the enhanced contaminant destruction in the system, [48] and it was suggested that successive production of sulphate and hydroxyl radicals can take place. [49] In a combined formulation of persulphate with hydrogen peroxide, the latter can degrade the contaminant to more reactive by-products, whereas persulphate provides a longer lasting treatment for deeper and more recalcitrant contamination.…”
Section: Combined Formulation Of Persulphate and Hydrogen Peroxide Fomentioning
confidence: 99%
“…A multiradical attack mechanism was proposed to explain the enhanced contaminant destruction in the system, [48] and it was suggested that successive production of sulphate and hydroxyl radicals can take place. [49] In a combined formulation of persulphate with hydrogen peroxide, the latter can degrade the contaminant to more reactive by-products, whereas persulphate provides a longer lasting treatment for deeper and more recalcitrant contamination.…”
Section: Combined Formulation Of Persulphate and Hydrogen Peroxide Fomentioning
confidence: 99%
“…Hydrogen peroxide and peroxydisulfate react together to form oxygen according to the equation (42,162) where equations (3), ( 5), and (6) are not simple steps.…”
Section: H Hydrogen Peroxidementioning
confidence: 99%
“…Based on the previous studies , the removal of NO from flue gas by using the dual oxidant (H 2 O 2 /S 2 normalO82) solution was very complicated. The SO4, derived from the thermal decomposition of the persulfate, can stimulate the formation of HO• and hydroperoxyl radical (HO 2 •).…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…The dual oxidant composed of H 2 O 2 and Na 2 S 2 O 8 attracts the widely attention, because which has the advantages of the low cost of hydrogen peroxide and the strong oxidation ability of sodium persulfate, and will not cause secondary pollution to the environment. The existing studies have showed that the hydroxyl free radicals (HO•) and sulfate free radicals ( SO4) coexisted in the dual oxidant system have a synergistic effect on the oxidation of pollutants. At present, Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation